2010
DOI: 10.1136/vr.c3155
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus serosurveillance in horses in Doñana, Spain, 2005 to 2008

Abstract: WEST Nile virus (WNV) activity has been recognised in southern Europe for decades, but evidence of WNV circulation in Spain has only recently been found, when serological and virological monitoring in populations of wild birds (Figuerola and others 2007, Höfle and others 2008, Jimenez-Clavero and others 2008, horses (Jimenez-Clavero and others 2007) and human beings (Bofill and others 2006, Kaptoul and others 2007) was carried out. However, the lack of observed bird mortalities and the practical absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 10 publications
4
20
2
Order By: Relevance
“…In the second survey, IgG seroprevalence within the 36 infected herds was 51.7% (46/89). All IgM-positive horses and 23 (34%) of 68 clinically healthy horses had antibodies against WNV by blocking ELISA and SNT, indicating intense local transmission in 2010, which contrasts with previous observations ( 2 ). …”
contrasting
confidence: 88%
“…In the second survey, IgG seroprevalence within the 36 infected herds was 51.7% (46/89). All IgM-positive horses and 23 (34%) of 68 clinically healthy horses had antibodies against WNV by blocking ELISA and SNT, indicating intense local transmission in 2010, which contrasts with previous observations ( 2 ). …”
contrasting
confidence: 88%
“…This area is considered one of the most important and outstanding protected spaces in Europe and is a major wintering and stopover area for migratory birds. Previous studies performed in this area have documented the circulation of WNV between resident birds [19], [29] and horses [30]. The presence of WNV, Usutu virus (USUV) and other flaviviruses in various mosquito species were detected during the sampling period for the present study [20], [21], although no case of WNV-related illness was reported.…”
Section: Methodssupporting
confidence: 49%
“…In particular, WNV has become widespread [22-25] and disease outbreaks have occurred when epizootic vectors transmit this virus from birds to horses or humans [26]. Wetlands are linked to endemic WNV circulation [27] and here we study two wetlands in SW Spain where: 1) WNV circulation since at least 2003 has been documented regularly in resident birds [28,29], horses [30] and humans [31]; 2) there is a great abundance of several mosquito species potentially involved in disease transmission [32,33] (Table  1); and 3) outbreaks of WNV in humans and horses have been reported from a neighbouring province [34-36]. In addition, the mosquito-borne flavivirus Bagaza has been detected in the surrounding area [37], there is a high incidence of Dirofilaria immitis and the potential malarial vector Anopheles atroparvus is abundant (Table  1).…”
Section: Introductionmentioning
confidence: 99%